AN-VR-BE. A Randomized Controlled Trial for Reducing Fear of Gaining Weight and Other Eating Disorder Symptoms in Anorexia Nervosa through Virtual Reality-Based Body Exposure - Bruno Porras‐Garcia; Marta Ferrer‐García; Eduardo Serrano‐Troncoso; Marta Carulla‐Roig; Pau Soto-Usera; Helena Miquel-Nabau; Laura Fernández-Del Castillo Olivares; Rosa Marnet-Fiol; Isabel de la Montaña Santos-Carrasco; Bianca Borszewski; Marina Díaz‐Marsá; Isabel Sánchez; et al. (2021)
In vivo body exposure therapy is considered an effective and suitable intervention to help patients with anorexia nervosa (AN) reduce their body image disturbances (BIDs). However, these interventions have notable limitations and cannot effectively reproduce certain fears usually found in AN, such as the fear of gaining weight (FGW). The latest developments in virtual reality (VR) technology and embodiment-based procedures could overcome these limitations and allow AN patients to confront their FGW and BIDs. This study aimed to provide further evidence of the efficacy of an enhanced (by means of embodiment) VR-based body exposure therapy for the treatment of AN. Thirty-five AN patients (16 in the experimental group, 19 in the control group) participated in the study. FGW, BIDs, and other body-related and ED measures were assessed before and after the intervention and three months later. The experimental group received treatment as usual (TAU) and five additional sessions of VR-based body exposure therapy, while the control group received only TAU. After the intervention, ED symptoms were clearly reduced in both groups, with most of the changes being more noticeable in the experimental group. Specifically, after the intervention and at follow-up, significant group differences were found in the FGW and BIDs, with the experimental group showing significantly lower values than the control group. The current study provides new insights and encouraging findings in the field of exposure-based therapies in AN. VR technology might improve research and clinical practice in AN by providing new tools to help patients confront their core fears (i.e., food- or weight-related cues) and improve their emotional, cognitive, and behavioral responses to their body image.